Supervisi Kepala Sekolah Dalam Mengembangkan Kompetensi Guru SMP Negeri Se-Kecamatan Janapria Kabupaten Lombok Tengah - Mansur, Muhammad (Jurnal Ilmiah Mandala Education (JIME), 2022)
This study aims to: (1) find out and describe the implementation model of principal supervision in developing teacher competence, (2) know and describe the challenges of principal supervision in developing teacher competence, (3) know and describe the implications of the results of principal supervision in developing competence. teacher. This study uses a qualitative approach. The location of this research is SMPN 4 Janapria and SMPN 5 Janapria Lombok Tengah. Data was collected through observation, in-depth interviews, and documentation or (triangulation), while data analysis used the Milles & Huberman technique, namely; data collection, data reduction, data presentation, and drawing conclusions, as for testing the validity of the data, namely: credibility, transferability, dependence, and certainty.The results of this study show (1) the principal supervision model at the Janapria District Junior High School uses a clinical supervision model and a scientific supervision model, (2) the challenges faced by school principals in carrying out supervision activities are teacher readiness in administration which is still incomplete, delivery of material in the class is not in accordance with the plan, does not evaluate the learning activities carried out, the teacher lacks discipline, (3) Implications The results of supervision carried out by the principal can develop teacher competence in pedagogic competence, personality competence, professional competence and social competence.